Prevalence of cattle trypanosomosis in slaughterhouses and farms in Benin and impact on hematocrit in cattle - Soha, Arnaud; Dotche, Ignace; Achade, Germain; Dougnon, Jacques; Karim, Issaka YA; Farougou, Souaïbou; Kpodekon, Marc (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The present study aimed to determine the prevalence of bovine trypanosomosis in Benin. Materials and Methods: For this purpose, the blood samples were taken from 932 cattle: 573 from slaughterhouses and 359 from the farms of the targeted divisions. After the blood samples, thick drops and blood smears were made. The capillary tubes filled with blood made it possible to determine the hematocrit in cattle. Results: The prevalence of trypanosomosis in farms (27.02%) was significantly higher (p < 0.001) than that of animals in slaughterhouses (16.75%). In farms, the prevalence was 38.55% during the rainy season against 16.67% in the dry season (p < 0.001). In slaughterhouses, prevalences were 10.99%, 17.58%, and 21.50%, respectively, in Bohicon, Cotonou/Porto-Novo, and Parakou. Hematocrit in slaughterhouses was 24.17% and 31.44%, respectively, in infested and non-infested animals. In farms, this rate was 22.85% in infested animals and 29.31% in non-infested animals (p < 0.05). Young cattle are more vulnerable to trypanosomosis than older cattle. Conclusion: Given the endemic situation of bovine trypanosomosis and its impact on the economy, this knowledge of the health status of cattle will help out to seek ways and alternatives to reduce the damage. J. Adv. Vet. Anim. Res., 7(1): 6-15, March 2020